The novel application of chitosan for the intranasal delivery of insulin - Hinchcliffe, Michael (1996)
The findings of this project have added to the pool of information reported in the literature regarding the application of the nasal route for the delivery of insulin and other peptide drugs. The preliminary studies reported in this project were apparently the first studies performed to investigate the potential use of chitosan in nasal delivery systems. Nasal delivery systems were investigated in rat and sheep models. The efficacy of chitosan as a nasal absorption enhancer for insulin was compared to that of several other compounds which had been reported in the literature to enhance nasasl [i.e. nasal] drug absorption. Erythrocyte haemolysis studies were also performed to evaluate the membrane damaging effects of the various compounds tested.